Contribution of Android and Gynoid Adiposity to Bone Mineral Density in Healthy Postmenopausal Thai Women - Sirianong Namwongprom (2018)
© 2018 Dual-energy X-ray absorptiometry (DXA) is one of the major tools for assessing the whole body and regional body composition and body adiposity. Various body composition parameters including android fat mass (AFM), gynoid fat mass (GFM), and android-to-gynoid fat ratio (AG fat ratio) obtained from whole body DXA can be used as a reliable surrogate marker for regional body composition analysis. This study aimed to explore the contribution of android and gynoid adiposity to bone mineral density (BMD) in healthy postmenopausal Thai women. This cross-sectional study enrolled 1448 healthy Thai women, ages 40–90 without medication history or known disease affecting the BMD. Lumbar spine (LS), total femur, and femoral neck BMDs, AFM, GFM, and AG fat ratio were measured by DXA. To evaluate the contribution of android and gynoid adiposity with various measures of BMDs, univariable and multivariable linear regression analyses were used to estimate the regression coefficients. AFM, GFM, and AG fat ratio had a significant positive association with BMD of all measured sites (p < 0.001) in the univariate analysis. The strongest association was found between AG fat ratio and LS BMD (β = 0.156, p ≤ 0.001). In multivariate linear regression analysis, the results continued to show a positive association between AFM and GFM at all skeletal sites after adjusting for age, height, and total body lean mass. Relationship between AG fat ratio and BMD was found only in LS region. GFM had a strongest positive effect with BMD at the LS, total femur, and femoral neck regions. Higher android and gynoid adiposity was associated with higher BMD. GFM rather than AFM shows the strongest positive association with BMDs in postmenopausal Thai women.